Late Effects of 1H + 16O on Short-Term and Object Memory, Hippocampal Dendritic Morphology and Mutagenesis - Kiffer, Frederico; Alexander, Tyler; Anderson, Julie; Groves, Thomas; McElroy, Taylor; Wang, Jing; Sridharan, Vijayalakshmi; Bauer, Michael; Boerma, Marjan; Allen, Antiño (Frontiers in Behavioral Neuroscience, 2020)
The space extending beyond Earth’s magnetosphere is subject to a complex field of high-energy charged nuclei, which are capable of traversing spacecraft shielding and normal tissue, inducing dense ionization events. The central nervous system is a major area of concern for astronauts who will be exposed to the deep-space radiation environment on a mission to Mars, as charged-particle radiation has been shown to elicit changes to the dendritic arbor within the hippocampus of rodents, and related cognitive-behavioral deficits. We exposed six-month-old male mice to whole-body 1H (0.5 Gy; 150 MeV/n; 18-19 cGy/minute) and an hour later to 16O (0.1Gy; 600 MeV/n; 18-33 Gy/min) at NASA’s Space Radiation Laboratory as a galactic cosmic ray-relevant model. Animals were housed with bedding which provides cognitive enrichment. Mice were tested for cognitive behavior nine months after exposure to elucidate late radiation effects. Radiation induced significant deficits in novel object recognition and short-term spatial memory (Y-maze). Additionally, we observed opposing morphological differences between the mature granular and pyramidal neurons throughout the hippocampus, with increased dendritic length in the dorsal dentate gyrus and reduced length and complexity in the CA1 subregion of the hippocampus. Dendritic spine analyses revealed a severe reduction in mushroom spine density throughout the hippocampus of irradiated animals. Finally, we detected no effect of radiation on single-nucleotide polymorphisms in immediate early genes, and genes involved in inflammation but found a higher variant allele frequency in the antioxidant thioredoxin reductase 2 loci.